Havard Business Review's 10 Must Reads on Managing People - Harvard Business Review (Boston Harvard Business Review Press, 2011)
If you read nothing else on managing people, read these 10 articles (featuring ?Leadership That Gets Results,? by Daniel Goleman). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you maximize your employees' performance.
Includes bibliographical references and index
Keywords: Supervision of employees